The anatomy and ontology of organizational power as a fractal metaphor: A philosophical approach - Amir Forouharfar (Cogent Business & Management, 2020)
Fractal metaphor could be introduced to organization studies to elaborate on those organizational concepts that call for self-organization, self-similarity, similarity persistence in different organizational levels, symmetrical expansion, homogeneous discipline and quality, omnipresent controlling measures, and growth, as well as the organizational processes and procedures that require recursion. Organizational power is an abstract entity which could precisely be explained via a metaphorical fractal. Thus, Sierpinski Triangle, a familiar geometrical fractal has been applied in the paper with the purpose to unfold the fractal characteristics of the power within organizations. Such an approach presumes power characteristics as hierarchical, pyramidal, distributive, recursive, accumulative, dependent, comparative, and unequal. The discussions through the paper could contribute to future organization theorists to form an idea on two ubiquitous concepts of organizational power: directionality and dimensionality. Moreover, the paper theorizes the triangular combination of need, interest, and relationship as ontological elements of potential power and a fourth entity (enforcement) in combination with the three previous elements as the necessary elements of every pragmatic power.
Keywords: 650; fractal concept; formal power; informal power; fractal power; fractal organization; fractal organization theory; organizational power ontology; organizational power philosophy